EDUCATIONAL DISPARITIES AMONG THE DISTRICTS OF PUNJAB (PAKISTAN) - Muhammad Qasim , Dr. Muhammad Zafar Iqbal , Dr. Gulzar Ahmad , Muhammad Qasim Ali (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Present study investigates the status of education and educational disparities across the districts of Punjab. There are 36 districts in Punjab province; we have calculated Education Index (EI) for thirty-five districts of Punjab, one district Chiniot is excluded due to some data constraints. Districts have been ranked based on their values of EI. The results of our study indicate that huge educational disparities exist in terms of EI across the districts of Punjab. Some districts like Rawalpindi and Lahore have high educational status with high EI values whereas some districts like Bahawalpur, Bahawalnagar, Dera Gazi Khan, Rahim Yar Khan, Lodhran and Rajanpur are lagging behind education with low EI values. Moreover, districts that have more distance from two capital cities Islamabad and Lahore have lower EI values. It indicates that may public provision of social services have remained in favor of those districts that are much closer to capital cities as compared to other districts. Policy to increase administrative units may reduce disparities in education among the districts of Punjab. Therefore, the districts with poor educational status required policy interventions to reduce educational disparities in Western and Southern regions of Punjab. Because the dismissal prevailing situations can create severe rivalry and distrust among different regions within Punjab Province.